Research into Practice: Cultural and intercultural awareness. (9th January 2015) - Baker, Will
<x content-type="archive" xml:space="preserve">Abstract</x> This article examines the role of cultural awareness (CA) and intercultural awareness (ICA) in classroom theory and practice. CA and ICA can be roughly characterised as an awareness of the role of culture in communication with CA focused on national cultures and ICA on more dynamic and flexible relationships between languages and cultures. There will be a consideration of findings from CA and ICA research that have not been well applied, those that have been well applied and those that have been over-applied to classrooms. In particular, it will be argued that CA and ICA are more prevalent in pedagogic theory, and to a lesser extent policy, than they are in practice. While the cultural dimension to language learning is now fairly mainstream, where elements of CA and ICA are applied or translated into the classroom they typically take the form of comparisons between national cultures, often in essentialist forms. There is still little evidence of classroom practice that relates to the fluid ways cultures and languages are related in intercultural communication, especially for English as a lingua franca or other languages used on a global scale.